Pleiotropic functions of TNF-? in the regulation of the intestinal epithelial response to inflammation - Leppkes, Moritz; Roulis, Manolis; Neurath, Markus; Kollias, George; Becker, Christoph (International Immunology, 2014)
An important function of intestinal epithelial cells (IECs) is to maintain the integrity of the mucosal barrier. Inflammation challenges the integrity of the mucosal barrier and the intestinal epithelium needs to adapt to a multitude of signals in order to perform the complex process of maintenance and restitution of its barrier function. Dysfunctions in epithelial barrier integrity and restoration contribute to the pathogenesis of inflammatory bowel diseases (IBDs) such as Crohn's disease and ulcerative colitis. Mucosal healing has developed to a significant treatment goal in IBD. In this review, we would like to highlight physiologic and pathologic adaptations of the intestinal epithelium to inflammation, exemplified by its responses to TNF-?. A large body of literature exists that highlights the diverse effects of this cytokine on IECs. TNF-? modulates intestinal mucus secretion and constitution. TNF-? stimulation modulates paracellular flow via tight junctional control. TNF-? induces intracellular signaling cascades that determine significant cell fate decisions such as survival, cell death or proliferation. TNF-? impacts epithelial wound healing in ErbB- and Wnt-dependent pathways while also importantly guiding immune cell attraction and function. We selected important studies from recent years with a focus on functional in vivo data providing crucial insights into the complex process of intestinal homeostasis.
EVALuna2:1867